Detection of Pathogenic and Beneficial Microbes for Roselle Wilt Disease - Wang, Chih-Wei; Yu, Yu-Hsiang; Wu, Chun-Yao; Feng, Ru-Ying; Tandon, Kshitij; Chen, Ying-Lien; Tang, Sen-Lin (Frontiers in Microbiology, 2021)
Wilt disease of roselle (Hibiscus sabdariffa L.) is common in Taiwan; however, the causative agent remains unknown. The stems of wilted roselle are browned, slightly constricted, and covered by white aerial hyphae, suggesting that potential pathogens may originate from soil. To identify the potential pathogens, we conducted a rhizosphere microbiota survey in phenotypically healthy and diseased plants through fungal internal transcribed spacer (ITS) and bacterial 16S rRNA amplicon sequencing for uncovering the microbial compositions in the roselle rhizosphere. The fungal family Nectriaceae exhibited significantly higher abundance in diseased rhizospheres than in healthy rhizospheres, and this bacterial community was more specific to geography (i.e., plot-dependent) than to rhizosphere disease status. However, a few bacterial groups such as Bacilli were associated with the healthy rhizosphere. Fusarium species were the most dominant species of Nectriaceae in the survey and became the main target for potential pathogen isolation. We successfully isolated 119 strains from diseased plants in roselle fields. Koch’s postulates were used to evaluate the pathogenicity of these strains; our results indicated that Fusarium solani K1 (FsK1) can cause wilting and a rotted pith in roselles, which was consistent with observations in the fields. This is the first demonstration that F. solani can cause roselle wilt in Taiwan. Furthermore, these newly isolated strains are the most dominant operational taxonomic units detected in ITS amplicon sequencing in diseased rhizospheres, which serves as further evidence that F. solani is the main pathogen causing the roselle wilt disease. Administration of Bacillus velezensis SOI-3374, a strain isolated from a healthy roselle rhizosphere, caused considerable anti-FsK1 activity, and it can serve as a potential biocontrol agent against roselle wilt disease.